Exercise addiction: an update - Ordu, Fatih (Journal of Dependence, 2022)
Exercise provides important contributions to the development of physical, mental and psychosocial health and the treatment of psychopathological processes. Addiction is process that disrupts the quality of life of individuals with repetitive patterns. Exercise addiction is the loss of control over exercise habits that will impair personal, social and professional adaptation. It is expected that related symptoms will be observed along with excessive exercise. It is behavioral addiction. There are biopsychosocial models proposed to contribute to the explanation and evaluation of exercise addiction. Although there are differences in the studies, its prevalence is accepted to be at the level of 3%. Exercise addiction has not been included as a psychological disorder in official classification systems until now, as there is insufficient evidence to establish the diagnostic criteria. The Exercise Addiction Inventory (EAI) and Exercise Addiction Scale-21 (EDS-21) were developed to reach the evidence. Discussions on the subject continue for various reasons such as conceptualization, research method and sampling. Considering personality traits and possible psychopathological features may contribute to a better understanding of exercise addiction. As the discussions continue, it has been evaluated that there are processes that need clarification.